2023
DOI: 10.53502/ornk7518
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soil Biostimulant Application on Protein and Carbohydrate Content in Per-ennial Ryegrass (Lolium Perenne L.)

Waldemar Zielewicz,
Barbara Wróbel,
Wojciech Stopa
et al.

Abstract: Article infoOne of the elements of modern plant fertilization systems is soil biostimulants. Like fertilizers, they provide plants with nutrients, and thanks to the content of additional substances (e.g. seaweed extracts, amino acids), plant development is affected. The aim of this study is to compare the effect of selected soil biostimulants and traditional P+K+Ca fertilization on changes in the content of crude protein (CP) and water soluble sugars (WSC) in perennial ryegrass (Lolium perenne L.) cv. Anna. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
0
1
Order By: Relevance
“…Sulewska et al [68] noted that biostimulant application led to a similar fat content in dry weight of rape seeds as fertilization with conventional P and K. This was in line with the results of our study, where no significant difference was proven between NS and CL variants. Zielewicz et al [69] observed a 7% increase in crude protein in ryegrass sward when a biostimulant was used, but no evidence for this increase was found in our results, although the crops were different. In addition, Mo żd żer et al [70] found that treatment of slurry with a stabilizer and PK fertilization increased the macro-elements' concentrations in winter rape and spring wheat grain; however, the significant qualitative parameter improvement was not confirmed in our results when the stabilizer was used.…”
Section: Discussioncontrasting
confidence: 95%
“…Sulewska et al [68] noted that biostimulant application led to a similar fat content in dry weight of rape seeds as fertilization with conventional P and K. This was in line with the results of our study, where no significant difference was proven between NS and CL variants. Zielewicz et al [69] observed a 7% increase in crude protein in ryegrass sward when a biostimulant was used, but no evidence for this increase was found in our results, although the crops were different. In addition, Mo żd żer et al [70] found that treatment of slurry with a stabilizer and PK fertilization increased the macro-elements' concentrations in winter rape and spring wheat grain; however, the significant qualitative parameter improvement was not confirmed in our results when the stabilizer was used.…”
Section: Discussioncontrasting
confidence: 95%